Sulfate and thiosulfate transport in Escherichia coli K-12: evidence for a functional overlapping of sulfate- and thiosulfate-binding proteins. - Sirko, A (1995)
In Escherichia coli, sulfate and thiosulfate ions are transported by an ABC-type transporter consisting of both the membrane components (the products of cysT, cysW, and cysA genes) and the periplasmic binders (the products of cysP and sbp genes). The single cysP and sbp mutants are able to utilize both sulfate and thiosulfate as a sole sulfur source, while the inactivation of both genes leads to cysteine auxotrophy resulting from the block in the transport of both ions.